2021
DOI: 10.1007/s42853-021-00117-7
|View full text |Cite
|
Sign up to set email alerts
|

A Review on the Effect of Soil Compaction and its Management for Sustainable Crop Production

Abstract: Purpose Sustainable crop production could contribute to feed and fuel for the ever-increasing global population. The use of heavy agricultural machinery has improved the efficiency of farming operations and increased global food production since the 1950s. But their negative impact on soil includes changing soil structure resulting in deteriorating soil productivity and environmental quality is being noticed for several decades. The purpose of this review is to summarize and help to better unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
75
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(78 citation statements)
references
References 155 publications
1
75
1
1
Order By: Relevance
“…Soil BD is a vital indicator of soil degradation because it influences soil porosity, plant nutrient availability, and soil microorganism activity ( Recha et al, 2022 ). According to Shaheb, Venkatesh & Shearer (2021) , soil conservation measures decreased soil compaction, resulting in increased root development and length. Shaheb, Venkatesh & Shearer (2021) indicated that soil compaction reduced root biomass significantly.…”
Section: Discussionmentioning
confidence: 99%
“…Soil BD is a vital indicator of soil degradation because it influences soil porosity, plant nutrient availability, and soil microorganism activity ( Recha et al, 2022 ). According to Shaheb, Venkatesh & Shearer (2021) , soil conservation measures decreased soil compaction, resulting in increased root development and length. Shaheb, Venkatesh & Shearer (2021) indicated that soil compaction reduced root biomass significantly.…”
Section: Discussionmentioning
confidence: 99%
“…A handheld penetrologger Eijkelkamp (Eijkelkamp Soil & Water, Giesbeek, Netherlands) with a cone diameter of 10 mm and angle of 60° was used ( Figure 7 b). Soil bulk density was evaluated [ 7 , 37 , 38 ] from dry soil weight [ 39 ]. Kopecky’s soil core samplers with a volume of 100 mL were used to collect the soil samples, Figure 7 c. The data experimentally measured were statistically evaluated using the GraphPad software.…”
Section: Methodsmentioning
confidence: 99%
“…This load cell is of a cylindrical industrial type for heavy-duty operation conditions. The body The resistance of soil acts on the blades which rotate the horizontal and vertical levers (7,8) around the pivot (4), as shown by orange arrows. Cutting blade fastening (5) allows the setting of various contact lengths of the blade with the soil and moments acting around the pivot.…”
Section: Design Of Soil Resistance Force Sensormentioning
confidence: 99%
See 1 more Smart Citation
“…Soil compaction increases soil density and decreases its porosity, mainly macro-porosity, impeding soil functions such as water infiltration, root penetration, and water and gas exchange. Crop productivity can be severely reduced by soil compaction as well (16). Soil erosion causes not only the loss of soil, but of carbon (C), nutrients, and pesticides as well.…”
Section: The Loss Of Soil Functions and Services In Degraded Agroecos...mentioning
confidence: 99%